Pertunjukan Madihin di Tembilahan Kabupaten Indragiri Hilir Provinsi Riau - Raihan Raihan; Laila Fitriah (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
The research discusses the Madihin Performance in Tembilan, Indrigiri Hilir Regency, Riau Province. The problem in this research is how is the Madihin Performance in Tembilahan, Indragiri Hilir Regency, Riau Province Based on the form of the Madihin performance in Tembilahan, Idragiri Hilir Regency, Riau Province. Madihin is a traditional art passed down from generation to generation brought by the Banjar people of Kalimantan to the island of Sumatra, namely Tembilahan, Indragiri Hilir Regency and Tembilahan is also one of the places where the majority of the population is inhabited by the Banjar tribe and contionues to grow and spread throughout Indragiri Hilir Regency. This research aims to analyze the Madihin Performance in Tembilahan, Indragiri Hilir Regency, Riau Province. The theory that researchers use is Y. Sumandiyo Hadi’s performance theory 2012. This research used qualitative methods and 5 research subjects as resource persons. The data collections techniques used are: Observation, interviews and documentation. The results of this research conclude that the Madihin Performance in Tembilahan, Indragiri Hilir Regency, Riau Province is an artistic performance using a typical Banjar musical instrument, namely the Flying Drum, which was brought and passed down from generation to generation from the Banjar people of Kalimantan to Tembilahan, Indragiri Hilir Regency, Riau Province, Which can be seen from Performance objects, performers, stage/stage, clothing, clothing, musical instruments and spectators that can be seen from the Madihin performance in Tembilahan, Indragiri Hilir Regency, Riau Province.